2024
DOI: 10.1139/er-2022-0118
|View full text |Cite
|
Sign up to set email alerts
|

Managing exploitation of freshwater species and aggregates to protect and restore freshwater biodiversity

Abstract: For millennia humans have extracted biological and physical resources from the planet to sustain societies and enable the development of technology and infrastructure. Growth in the human population and changing consumption patterns have increased the human footprint on ecosystems and their biodiversity, including in fresh waters. Freshwater ecosystems and biodiversity face many threats and it is now widely accepted that we are in a biodiversity crisis. One means of protecting and restoring freshwater biodiver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 170 publications
0
2
0
Order By: Relevance
“…Although discussions on the sustainable cities transition center on green infrastructure and nature-based solutions, these documents also advocate for sustainable materials and improved spatial planning that accounts for the impact of urban communities on nearby and distant ecosystems, following the metacoupling framework (Liu, 2017). Yet, the full reach of the threat posed by mining construction minerals to biodiversity remains uncertain due to knowledge and data gaps (Cooke et al, 2023;Torres, zu Ermgassen, et al, 2022). Our results show that current policies still fall short of clear statements and outcomes regarding the reporting and monitoring of mining threats, especially related to construction minerals.…”
Section: Hard Problems Concrete Solutionsmentioning
confidence: 87%
“…Although discussions on the sustainable cities transition center on green infrastructure and nature-based solutions, these documents also advocate for sustainable materials and improved spatial planning that accounts for the impact of urban communities on nearby and distant ecosystems, following the metacoupling framework (Liu, 2017). Yet, the full reach of the threat posed by mining construction minerals to biodiversity remains uncertain due to knowledge and data gaps (Cooke et al, 2023;Torres, zu Ermgassen, et al, 2022). Our results show that current policies still fall short of clear statements and outcomes regarding the reporting and monitoring of mining threats, especially related to construction minerals.…”
Section: Hard Problems Concrete Solutionsmentioning
confidence: 87%
“…For example, a study analysed the Chinese fishery-banning policy and suggested that fishery regulation bringing successful biodiversity outcomes requires adjusting regulations to local and regional needs (Chen et al, 2020). Another example of the research suggested the importance of transitioning to alternative food sources and assessing their potential issues before making conservation efforts for endangered freshwater fish (Cooke et al, 2023). Thus, policymakers should consider the potential shifts in consumers' food preferences resulting from the regulations before making decisions regarding regulation and enforcement.…”
Section: Introductionmentioning
confidence: 99%
“…The anguillid eel species, especially Anguilla japonica (Japanese eel), requires consumers' behavioural change as high consumer demand exacerbates the eel fishery (Cooke et al, 2023). It is decreasing worldwide and has been classified as Endangered on the IUCN Red List (Dekker, 2003) Pike et al 2020).…”
Section: Introductionmentioning
confidence: 99%